The immediate effects of ankle restriction using an elastic band on ground reaction force during a golf swing - Yi, K.; Kim, O. (Korean Journal of Sport Biomechanics, 2016)
Purpose: The purpose of this study was to analyze the immediate effects of ankle restriction with an elastic band on ground reaction force during a golf swing. Method: There were five subjects who were teaching pros with an average golf score of 75. A force platform (9281B, Switzerland) was used. The independent variable was the presence of an elastic band. The dependent variables were three-dimensional ground reaction forces to analyze the transfer of momentum with the timing, control and coordination of the three forces. A paired t-test within subject repeated measure design was used via an SPSS 20.0. Results: Wearing an elastic band around one's ankles significantly makes shorter time differences between the moment of cross anterior / posterior forces and vertical force and median value of anterior / posterior forces during the backswing, between medial and lateral maximum and anterior / posterior force from the top of the back swing to the mid down swing, and creates an anterior / posterior maximum force. Conclusion: Wearing an elastic band around one`s ankles affects control and coordination between three dimensional forces, and anterior force power according to each phase of the golf swing.